The effects of pre-task music on exercise performance and associated psycho-physiological responses: a systematic review with multilevel meta-analysis of controlled studies - Delleli, Slaheddine; Ouergui, Ibrahim; Ballmann, Christopher Garrett; Messaoudi, Hamdi; Trabelsi, Khaled; Ardigò, Luca Paolo; Chtourou, Hamdi (Frontiers in Psychology, 2023)
This systematic review summarized the studies that examined the pre-task music effects on performance aspects and quantitatively analyzed their outcomes. A systematic search for controlled studies investigating the acute effects of pre-task music on physical performance, cognitive aspects and associated psycho-physiological responses was performed through Scopus, Pubmed, Web of Science and Cochrane Library databases up to 17 May 2023, with thirty studies fulfilled the inclusion criteria. Data was analyzed using the robust multilevel meta-analysis model of standardized mean difference "SMD" with 95% confidence intervals (95%CI) and prediction intervals (PI) were reported. Pre-task music induced improvements of completion time [SMD= -0.24; 95% CI= -0.46 to -0.01; PI= -0.82 to 0.35; p=0.04], relative mean power (RMP) [SMD= 0.38; 95% CI=0.16 to 0.60; PI= -0.36 to 1.12; p=0.003] and fatigue [SMD= -0.20; 95% CI= -0.32 to -0.09; PI= -0.36 to -0.05; p=0.01], moderate effects on relative peak power (RPP) [SMD= 0.53; 95% CI= 0.21 to 0.85; PI= -0.42 to 1.48; p=0.005], and high effect on feeling scale (FS) [SMD= 2.42; 95% CI= 0.52 to 4.31; PI= -11.43 to 16.26; p=0.03]. Greater benefits were recorded in jumping performance in males than females (p=0.01), and for active than trained subjects for completion time (p=0.02), RPP (p=0.02) and RMP (p=0.03). Larger benefits were obtained for FS post-warming up than after testing (p=0.04). Self-selected music induced greater effects than pseudo- and pre-selected for performance decrement index (p=0.05) and FS (p=0.02). It could be concluded that pre-task music improved psychological responses and fatigue-related symptoms associated with exercise performance enhancement.